Peran Guru PAI melalui Pendekatan Emosional dalam Meningkatkan Rasa Percaya Diri Siswa di Kelas - Safutra, Novrian Eka; Ramadhani, Sandrina; Takrim, Donna; Mukjizat, Lailatul; Wigati, Indah; Oviyanti, Fitri (Riwayat: Educational Journal of History and Humanities, 2025)
This study aims to analyze the role of Islamic Religious Education (PAI) teachers in enhancing students self-confidence through the implementation of emotional approaches in classroom learning. PAI teachers act not only as transmitters of religious knowledge but also as spiritual and emotional mentors who understand students psychological conditions. The study employs a library research method, drawing upon relevant academic sources such as journals, books, and previous research findings. The findings indicate that emotional approaches applied by PAI teachers through empathy, positive communication, motivation, and exemplary conduct significantly enhance students self-esteem and self-efficacy. Moreover, a supportive and emotionally safe classroom environment fosters a sense of belonging and appreciation among students, which forms the foundation for confidence building. Therefore, the emotional approach practiced by PAI teachers not only strengthens students affective and spiritual dimensions but also contributes to developing positive character and a strong sense of self-assurance in both academic and social contexts.